PROBLEMATIKA EKSEKUSI HARTA PAILIT DI LUAR YURISDIKSI INDONESIA DALAM PERKARA KEPAILITAN LINTAS NEGARA - Neysa Tania; Gunardi Lie; Moody R Syailendra (PROSIDING SERINA, 2021)
The world economy has integrated into the free trade era. Under this, the boundaries of conducting business transactions in these countries are no longer an obstacle. The existence of transnational elements also brings risks in the economic field; such as when a debtor becomes insolvent and bankrupt. The fulfillment of international elements in a cross-border bankruptcy case will certainly link the legal system of a country with other countries concerned. Moreover, it concerns the authority to execute bankruptcy assets outside the jurisdiction of Indonesia. Bearing in mind that each country has its own bankruptcy law regulations, each country is obliged to respect the laws of other countries following the principle of the jurisdiction of the country itself. Due to the sovereignty principle, the resolution of cross-border insolvency cases often becomes inefficient and effective. Moreover, because Indonesia still adheres to the territorial principle, the debtor can be bankrupted even though there are assets abroad, which makes it difficult for the curator to settle the debtor's assets. In addition, Indonesia is also not bound by international agreements regarding cross-border insolvency so that the inefficient regulation and settlement of cross-border insolvency cases can hamper the flow of receivables payments to all or part of certain creditors so that the smoothness, stability, and conduciveness of cross-border business activities can be disrupted. This research is a normative juridical research with library research as its method to further examine the problems of execution of bankrupt assets outside the jurisdiction of the territory of Indonesia.